Quality of working life of nurses in emergency service and their influence on quality of care of the hospital Cayetano Heredia - Lima 2017 - Ortega-Soto, Alicia (2019)
To determine the influence of the quality of working life of nurses on the quality of care. A correlational study was carried out, with 46 Nursing professionals in the Emergency Service of the Hospital Cayetano Heredia - Lima 2017. A quality of life questionnaire was used in the work and guide of quality observation of Nursing care. For the inferential analysis we used the Pearson r correlation test. 93.5% (43 nurses) showed average quality of work life and 67.4% (31 nurses) provided good quality of care. On the other hand, a statistically significant relationship was found between the quality of working life and the quality of nursing care, with p≤0,000. And, the quality of nursing care is significantly related to institutional support for work (p≤0,010), Safety at work (p≤0,010), Integration at the workplace (p≤0,006), Satisfaction at work (P≤0,000), Well-being achieved through work (p≤0.007), Personal development (p≤0,019) and Leisure management (p≤0,003). The quality of work life of the nurses influences the quality of care of emergency service of the Hospital Cayetano Heredia - Lima.